2021
DOI: 10.3390/nu13124274
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Crocus sativus (Saffron) Intake on Top of Standard Treatment, on Disease Outcomes and Comorbidities in Patients with Rheumatic Diseases: Synthesis without Meta-Analysis (SWiM) and Level of Adherence to the CONSORT Statement for Randomized Controlled Trials Delivering Herbal Medicine Interventions

Abstract: Rheumatic diseases (RDs) are often complicated by chronic symptoms and frequent side-effects associated with their treatment. Saffron, a spice derived from the Crocus sativus L. flower, is a popular complementary and alternative medicine among patients with RDs. The present systematic review aimed to summarize the available evidence regarding the efficacy of supplementation with saffron on disease outcomes and comorbidities in patients with RD diagnoses. PubMed, CENTRAL, clinicaltrials.gov and the grey literat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 86 publications
0
13
0
Order By: Relevance
“…Saffron can prevent oxidative damage by a reduction in the concentration of endogenous ROS and a reduction in the production of pro-inflammatory biomarkers [ 118 , 119 ]. Crocin can improve cognitive disorders to some extent by targeting hippocampal apoptosis and oxidative stress [ 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…Saffron can prevent oxidative damage by a reduction in the concentration of endogenous ROS and a reduction in the production of pro-inflammatory biomarkers [ 118 , 119 ]. Crocin can improve cognitive disorders to some extent by targeting hippocampal apoptosis and oxidative stress [ 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…Modern pharmacology and molecular biology studies have verified that HSYA can exert anti-inflammatory, antioxidant ( He et al, 2021 ), and antiischemia reperfusion injury ( Bai et al, 2020 ) effects and is widely used in the treatment of acute or chronic cardiovascular and cerebrovascular diseases ( Xu et al, 2021 ; Geng et al, 2018 ). It has been shown to play a role in ameliorating cognitive impairment ( Zhang et al, 2021a ), rheumatic diseases ( Tsiogkas et al, 2021 ), and osteoporosis ( Wang et al, 2021b ) and regulating glucose and lipid metabolism ( Sun et al, 2021 ), providing new perspectives for exploring the development and application of HSYA in the health care industry ( Sun et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Published research indicated that saffron can slow down the oxidative damage reducing the concentrations of the ROS produced (Tsiogkas et al, 2021). The production in a great amount of ROS in MS patients may affect the antioxidant defense system of the CNS and can lead to further demyelination and loss of the neurons (Offen et al, 2004).…”
Section: Potential Therapeutic Effects Of Saffron In Multiple Sclerosismentioning
confidence: 99%